2022
DOI: 10.3390/app12031640
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Self-Prestressed RC Slabs with Fe-Based Shape Memory Alloy Rebar

Abstract: A lot of studies have been conducted to introduce self-prestress to structures using Fe-based shape memory alloys (Fe-SMAs). Technology to introduce self-prestress using Fe-SMAs can resolve the disadvantages of conventional prestressed concrete. However, most of the research to introduce a self-prestress force to a structure using Fe-SMAs has been focused on using Fe-SMAs for the repair and strengthening of aging structures. Therefore, in this paper, a study was conducted to introduce self-prestress into a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Yeon After investigation, few studies on SMA-reinforced slab members were found. Yeon et al [141] conducted a flexural test on unidirectional RC slabs with Fe-SMA reinforcement as the tensile steel bars and evaluated the influence of the recovery stress of Fe-SMA reinforcement on the flexural performance of the slabs. The results showed that the number and width of bending cracks decreased with Fe-SMA reinforcement, which was mainly due to the prestressing effect of the recovery stress generated by the Fe-SMA reinforcement.…”
Section: Sma-reinforced Shear Walls and Concrete Slabsmentioning
confidence: 99%
“…Yeon After investigation, few studies on SMA-reinforced slab members were found. Yeon et al [141] conducted a flexural test on unidirectional RC slabs with Fe-SMA reinforcement as the tensile steel bars and evaluated the influence of the recovery stress of Fe-SMA reinforcement on the flexural performance of the slabs. The results showed that the number and width of bending cracks decreased with Fe-SMA reinforcement, which was mainly due to the prestressing effect of the recovery stress generated by the Fe-SMA reinforcement.…”
Section: Sma-reinforced Shear Walls and Concrete Slabsmentioning
confidence: 99%
“…Its application in the civil engineering and construction industries is to use shape memory effect to generate prestress inside the structure. The prestressing of Fe-Mn-Si shape memory alloys can enhance the flexural strength and cracking stress of concrete structures [16][17][18]. When Fe-Mn-Si shape memory alloys are applied to prestressed structures, researchers pay more attention to the magnitude of the prestress generated by the material.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the method of introducing prestress using SMA, it is possible to simply introduce prestress to the concrete member only by heating SMA without an anchoring device and jacking device, unlike the conventional prestress method. Moreover, unlike conventional bonded prestressed concrete, concrete members to which prestress is introduced through SMA can recover the initial recovery stress through simple reactivation even if recovery stress is lost due to various causes such as drying shrinkage and creep of concrete, and SMA relaxation [23].…”
Section: Introductionmentioning
confidence: 99%